THE LANGUAGE DEVELOPMENT IN INDONESIAN PRESIDENTIAL DECREES - Wulandari, Desty; Datang, Frans Asisi (UI Scholars Hub, 2019)
President has an authority to establish policies in order to run the government, one of which is through Keputusan Presiden Republik Indonesia (Indonesian Presidential Decree). As written documents, the Decrees have language development which can be seen from the writing patterns. Therefore, this study aims to examine the writing patterns of Decrees from time to time to support forensic linguistic study, such as document forgery analysis. We took sixteen Presidential Decrees from 1945 to 2018 as the data then analyzed them by using qualitative method. The data were obtained from the National Archives of the Republic of Indonesia and the official website of the Cabinet Secretariat of the Republic of Indonesia (www.sipuu.setkab.go.id). This study indicates that language development in Indonesian Presidential Decrees is found in the structure of the Decrees, diction, and sentence structure. On the Decree structure, 1945 and 1946 Decrees contain one long sentence to explain the intent, whereas in the 1947—2018 Decrees, intents are elaborated in several clauses. Additionally, there are various types of diction used in the consideration sections. On the syntax, various types of sentences can be found in the Decrees. 1940s Decrees contain simple sentences and complex sentences while 1950s—2010s Decrees contain simple sentences, complex sentences, compound sentences, and mixed sentences.